Herbs for diabetes and neurological disease management: Research and advancements - Kumar V.; Veeranjaneyulu A. (My University, 2025)
This new volume provides a plethora of new information about potential medicinal herbs and their usefulness in treating diabetes and neurological diseases. Most large multinational companies are interested and engaged in the commercialization of herb-based formulations, and consumers continue to seek natural-based therapies. Herbs for Diabetes and Neurological Disease Management provides insight into plant-based novel molecules targeted for diabetes and neurological disorders. It looks at a selection of herbs that have proven effective in the management of diabetes and neurological disorders, including migraine, epilepsy, memory disorders, depression, and more. Divided into ten chapters focusing on diabetes and its macro- and microvascular complications (migraine, epilepsy, memory disorders, depression and other neuropsychiatric disorders), this book is structured to provide a source of reliable information and enrich the knowledge of readers. Each chapter briefly explains the epidemiology and pathophysiology of the disease state and the possible role of herbal drugs in the prevention of the particular disease. The reported pharmacological activities and possible mechanism of action of herbal drugs are also discussed in detail, which makes this book informative and unique. This new volume will be a reliable reference complementing the substantial information on the use of herbal drugs in diabetes and neurological disorders that serve as the pillars of drug discovery and development. © 2018 by Apple Academic Press, Inc.